Benefits and barriers to following HACCP-based food safety programs in childcare centers - Riggins, Lynn D.; Barrett, Betsy (My University, 2008)
Before HACCP can be implemented in childcare centers, it is important to identify existing prerequisite programs and implementation barriers. Studying the food safety beliefs and perceptions of directors and foodservice employees in childcare centers is the first step in the process. On the basis of reviewing previous Health Belief Model and food safety research, an instrument was developed that focused on childcare centers, the children at the childcare centers, and HACCP-based food safety behaviors. The population for this study included childcare centers directors and foodservice employees in six Midwestern states. Overall, respondents agreed that they could follow HACCP-based programs; however, foodservice employees indicated more confidence in their abilities than did directors. The least implemented prerequisite programs were those related to equipment maintenance, food safety training, and kitchen operation procedures. For all nine prerequisite programs, significant differences based on certification status were found. It appears that childcare centers could easily adapt existing programs to follow a HACCP-based food safety program, but additional food safety training is needed. Future research conducted with directors and employees of childcare centers should assess knowledge levels and attitudes about HACCP-based food safety programs.
Keywords: HACCP; Childcare centers; Food safety; Health belief model